EFFECT OF COCONUT WATER SOAKING LENGTH ON Pterocarpus indicus L. SEED GERMINATION - Maria Agustina Manurung; M Mardhiansyah; Evi Sribudiani (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2021)
Forests in Indonesia have very diverse species of trees. One of them is Pterocarpus indicus L. Pterocarpus indicus L.. is a pioneer tree that grows well in open areas. Pterocarpus indicus L. has fast growth and strong wood so that it can be used in greening activities in the community and on the highway. The purpose of this study was to determine the effect of coconut water soaking length on Pterocarpus indicus L. seed germination and knowing the best long immersion time of Pterocarpus indicus L. seeds using coconut water in improving seed quality. This study uses a completely randomized design (CRD) method consisting of five treatments and three replications. The results showed that immersion with a mixture of coconut water affected the increase in the quality of Pterocarpus indicus L. seed germination. The best immersion time of Pterocarpus indicus L. seeds in a mixture of coconut water for 18 hours showed the results of the required time for germination seeds to reach 80% for 11 days, the increase in sprout height was 9,45 cm and the number of leaves as much as 7,85 strand